Regional variation of white matter development in the cat brain revealed by ex vivo diffusion MR tractography. Issue 54 (24th August 2016) - Dai, Guangping; Das, Avilash; Hayashi, Emiko; Chen, Qin; Takahashi, Emi
Abstract: Three‐dimensional reconstruction of developing fiber pathways is essential to assessing the developmental course of fiber pathways in the whole brain. We applied diffusion spectrum imaging (DSI) tractography to five juvenile ex vivo cat brains at postnatal day (P) 35, when the degree of myelination varies across brain regions. We quantified diffusion properties (fractional anisotropy [FA] and apparent diffusion coefficient [ADC]) and other measurements (number, volume, and voxel count) on reconstructed pathways for projection (cortico‐spinal and thalamo‐cortical), corpus callosal, limbic (cingulum and fornix), and association (cortico‐cortical) pathways, and characterized regional differences in maturation patterns by assessing diffusion properties. FA values were significantly higher in cortico‐cortical pathways within the right hemisphere compared to those within the left hemisphere, while the other measurements for the cortico‐cortical pathways within the hemisphere did not show asymmetry. ADC values were not asymmetric in both types of pathways. Interestingly, tract count and volume were significantly larger in the left thalamo‐cortical pathways compared to the right thalamo‐cortical pathways. The bilateral thalamo‐cortical pathways showed high FA values compared to the other fiber pathways. On the other hand, ADC values did not show any differences across pathways studied. These results demonstrate that DSI tractography successfully depicted regional variations of white matter tracts during development when myelination is incomplete. Low FA and high ADC values in the cingulum bundle suggest that the cingulum bundle is less mature than the others at this developmental stage.